Development of Entrepreneurial Leadership Competencies Among Malaysian University Students - Bagheri, Afsaneh (2011)
Recent developments in entrepreneurial leadership raised many questions about how to develop entrepreneurial leadership competencies particularly, in university students as prospective entrepreneurial leaders. In particular, there is not enough knowledge on the specific competencies enabling university students to lead entrepreneurial activities, factors motivating them to learn and develop their entrepreneurial leadership competencies, the process of their entrepreneurial leadership competencies, and the roles that university entrepreneurship programs play in developing the students’ entrepreneurial leadership competencies. This research attempted to answer these questions through employing qualitative research method. A sample of fourteen undergraduate entrepreneurial leaders defined as students successfully leading the university entrepreneurship clubs and activities for more than two semesters and four university entrepreneurship program coordinators was purposefully selected as the participants. The main technique for data collection was semi-structured interviews. The interviews lasted between 50 to 110 minutes and were recorded in a digital audio recorder. Once the interviews were conducted, they were labelled and transferred to NVIVO 8 software to be transcribed. The interviews transcribed in 48 hours after the actual interview was conducted. Then, the transcriptions were sent to the participants for content validity. Analysis of the data including the interview transcriptions and documents provided by the universities was carried out in two main phases. First, preliminary data analysis that was the process of data analysis conducted after obtaining each data. Second, thematic data analysis carried out by coding the data through open coding, axial coding, and selective coding. Analysis of the data revealed that student entrepreneurial leaders had two specific competencies that enabled them to lead university entrepreneurship clubs and activates including personal competencies and functional competencies. The dominant personal competencies of the student entrepreneurial leaders were: proactiveness, innovativeness, self-efficacy, love of challenges, and versatility. Functional competencies enabling student entrepreneurial leaders to successfully lead entrepreneurship clubs and activities were ability to create a caring interpersonal relationship, employing an enabling task delegation approach, and building self-confidence of their group members. Two main factors emerged as the significant motives for the student entrepreneurial leaders to learn and develop their entrepreneurial leadership competencies including internal factors which are personal interest and self-development and external factors including entrepreneurial learning opportunities and programs, entrepreneurial leadership task demands and expectations, problems and opportunities, and significant others. Student entrepreneurial leaders’ entrepreneurial leadership competencies developed through a continuous and gradual process of learning, change, and maturity in personal and interpersonal competencies that occurs through involvement in practicing leadership roles and tasks and requires executing a lot of endeavour, ambition, and perseverance. Thirty eight roles emerged as contributions of university entrepreneurship programs in developing student entrepreneurial leaders’ entrepreneurial leadership competencies which were organized in two clusters including student-related and program-related roles. Student-related roles contained enhancing personal and functional competencies of the students. Program-related roles reflected providing entrepreneurial learning opportunities (experiential learning, social interactive learning, observational learning and reflective learning), liking students to entrepreneurial industries, and having a holistic approach to develop students’ entrepreneurial competencies.